PENERAPAN MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE NUMBERE HEAD TOGETHER (NHT) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA BELAJARAN PPKN KELAS VIII-A SMP N 6 MATARAM - FITRI, RUHIL; RISPAWATI, RISPAWATI; ALHADIKA, MUHAMMAD; ISMAIL, M. (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This research aims to apply the Number Head Together (NHT) type cooperative learning model to increase student learning motivation in the Pancasila and Citizenship Education (ppkn) class VIII-A SMP N 6 Mataram. This research uses Classroom Action Research (Classroom Astion Research) with data collection techniques through observation, questionnaires and documentation. The stages in this research are initial observation, planning, action, observation and reflection. The subjects of classroom action research were students in class VIII-A of SMP 6 Mataram. The results of research in cycle I showed that the implementation of the Number Head Together (NHT) learning model was achieved at 50%, the level of student learning motivation was achieved at 54%. Furthermore, cycle II showed that the implementation of the Number Head Together (NHT) learning model was achieved at 83% and the level of student learning motivation was achieved at 65%. Furthermore, cycle III shows that the implementation of the Number Head Together (NHT) learning model has been implemented at 100% and the level of student learning motivation is 91%. ABSTRAKPenelitian ini bertujuan menerapkan model pembelajaran kooperatif learnig tipe Numbere Head Together (NHT) untuk meningkatkan motivasi belajar siswa pada mata pelajara Pendidikan Pancasila dan Kewarganegaraan (ppkn) kelas VIII-A SMP N 6 Mataram. Penelitian ini mengguakan Penelitian Tindakan Kelas (Classroom Astion Risearch) dengan tehnik pengumpulan data melalui observasi, angket,dan dokumentasi. Adapun tahapan dalam penelitian ini adalah observasi awal, perencanaann, tindakan, observasi dan refleksi. Subyek penelitian tindakan kelas adalah siswa kelas VIII-A SMP 6 Mataram. Hasil penelitian pada siklus I menunjukkan penerapan model pembelajaran Numbere Head Together (NHT) terlaksana sebesar 50%, tingkat motivasi belajar siswa terlaksana 54%. Selanjutnya pada siklus II menunjukkan penerapan model pembelajaran Numbere Head Together (NHT) terlaksanasebesar 83% dan tingkat motiwati belajar siswa terlaksana 65%. Selanjutnya pada siklus III menunjukkan penerapan model pembelajaran Numbere Head Together (NHT) terlaksanasebesar 100% dan tingkat motivasi belajar siswa 91%